Student lifestyle: physical activity and health - Lim M.S. ,; Shilko V.G. ,; Kim D.S. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determine the dynamics of interests and attitudes of student youth towards physical education, sports style and a healthy lifestyle over the past decade. Methods and structure of the study. The presented work presents data from sociological surveys conducted among students of the TSU Research Institute between 2013 and 2023. The aim of these surveys was to study their attitudes towards a healthy lifestyle, physical culture, and sports. Results and conclusions. The examination allowed us to discern alterations in the preferences and requirements of students regarding participation in various sports and physical activities, and also to evaluate the significance of physical exercise in enhancing the health and physical condition of students in the two contrasting timeframes.